Form(s)-of-life. Agamben's reading of Wittgenstein and the potential uses of a notion - Saidel, Matías Leandro (2014)
Giorgio Agamben and Ludwig Wittgenstein seem to have very little in common: the former is concerned with traditional ontological issues while the latter was interested in logics and ordinary language, avoiding metaphysical issues as something we cannot speak about. However, both share a crucial notion for their philosophical projects: form of life. In this paper, I try to show that, despite their different approaches and goals, form of life is for both a crucial notion for thinking ethics and life in-common. Addressing human existence in its constitutive relation to language, this notion deconstructs traditional dichotomies like bios and zoé, the cultural and the biological, enabling both authors to think of a life which cannot be separated from its forms, recognizing the commonality of logos as the specific trait of human existence. Through an analogical reading between both theoretical frameworks, I suggest that the notion of form-of-life, first elaborated by Wittgenstein to address human production of meaning, becomes the key notion in Agamben´s affirmative thinking since it enables us to consider the common ontologically in its relation to Human potentialities and to grasp a new, common use of the world and ourselves.